Effect of Cohesive Properties on Low-Velocity Impact Simulations of Woven Composite Shells - Ferreira, Luis M. (2023)
The effect of the interface stiffness and interface strength on the low-velocity impact response of woven-fabric semicylindrical composite shells is studied using finite element (FE) models generated with continuum shell elements and cohesive surfaces. The intralaminar damage is accounted for using the constitutive model provided within the ABAQUS software, while the interlaminar is addressed utilising cohesive surfaces. The results show that the interface stiffness has a negligible effect on the force and energy histories for values between 101 N/mm3 and 2.43 106 N/mm3. However, it has a significant impact on the delamination predictions. It is observed that only the normal interface strength affects the maximum impact force and the delamination predictions. Increasing its value from 15 MPa to 30 MPa resulted in an 8% growth in the maximum force, and a substantial reduction in the delaminated area. The obtained results serve as guidelines for the accurate and efficient computation of delamination. The successful validation of the FE models establishes a solid foundation for further numerical investigations and offers the potential to significantly reduce the time and expenses associated with experimental testing.